Dynamics of green productivity growth for major Chinese urban agglomerations. (15th June 2017) - Tao, Feng; Zhang, Huiqin; Hu, Jun; Xia, X.H.
Highlights: Green productivity growth was measured in major urban agglomerations of China. Technical progress is the main contributor to green productivity growth. Green and yellow cities were categorized by the criterion of eco-friendliness. Green innovators were identified from the sample cities. Determinants driving green productivity growth vary across urban agglomerations. Abstract: This paper employs the global Malmquist–Luenberger productivity index to measure and decompose green productivity growth for three major urban agglomerations in China over the period 2003–2013. As the first study known to focus on the green productivity of emerging cities in developing countries, the results show that technical progress, rather than efficiency improvements, is the main contributor to green productivity growth. Using the criterion of eco-friendliness, we categorize the cities into 'green' and 'yellow' city groups and identify 10 green innovators for the sample cities. The analysis also discusses the determinants of the drivers of green productivity growth and provides some useful policy implications.